A simple method to compare firing pin marks using stereomicroscope and Microsoft office (Windows 8) tools. (August 2017) - Suresh, R.
Graphical abstract: Highlights: Simple method to compare firing pin marks on fired shells. Fired shells examined under stereomicroscope & photographed. Using MS word picture tools, characteristic firing pin marks visualized. Crop & strip images into segments, side-by-side analysis done in word document. Matched pertinent marks to demonstrate firearm identification. Abstract: Pertinent marks of fired cartridge cases such as firing pin, breech face, extractor, ejector, etc. are used for firearm identification. A non-standard semiautomatic pistol and four .22 rim fire cartridges (head stamp KF) is used for known source comparison study. Two test fired cartridge cases are examined under stereomicroscope. The characteristic marks are captured by digital camera and comparative analysis of striation marks is done by using different tools available in the Microsoft word (Windows 8) of a computer system. The similarities of striation marks thus obtained are highly convincing to identify the firearm. In this paper, an effort has been made to study and compare the striation marks of two fired cartridge cases using stereomicroscope, digital camera and computer system. Comparison microscope is not used in this study. The method described in this study is simple, cost effective, transport to field study and can be equipped in a crime scene vehicle to facilitate immediate on spot examination. The findings may be highly helpful to the forensic community, law enforcement agencies and students.